2019
DOI: 10.3390/cryst9120614
|View full text |Cite
|
Sign up to set email alerts
|

Linear One-Dimensional Coordination Polymers Constructed by Dirhodium Paddlewheel and Tetracyanido-Metallate Building Blocks

Abstract: In this article, we describe the preparation of anionic heteronuclear one-dimensional coordination polymers made by dirhodium paddlewheels and tetracyanido-metallatate building blocks. A series of complexes of (PPh4)2n[{Rh2(µ-O2CCH3)4}{M(CN)4}]n (M = Ni (1), Pd (2), Pt (3)) formulae were obtained by reaction of [Rh2(μ-O2CCH3)4] with (PPh4)2[M(CN)4] in a 1:1 or 2:1 ratio. Crystals of 1−3 suitable for single crystal X-ray diffraction were grown by slow diffusion of a dichloromethane solution of the dirhodium com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…All the Rh-Rh distances are indicative of a single bond between Rh(II) ions. Rh-Rh and Rh-N distances are similar to those found in other related compounds such as (PPh 4 ) 2 n [{Rh 2 (µ–O 2 CCH 3 ) 4 }{M(CN) 4 }] n (M = Ni, Pd, Pt) [ 61 ], K n [Rh 2 (µ–O 2 CR) 4 Au(CN) 2 ] n (R = Me, Et) [ 59 ], (PPh 4 ) n [Rh 2 (µ–O 2 CR) 4 Ag(CN) 2 ] n (R = Me, Ph, CH 2 OEt) [ 60 ], (PPh 4 ) 2 {Rh 2 (μ–O 2 CCMe 3 ) 4 [Ag(CN) 2 ] 2 } [ 60 ], [K(18–crown–6)(H 2 O)] 2 n [K(18–crown–6)(H 2 O) 2 ] n [Rh 2 (µ–O 2 CPh) 4 Fe(CN) 6 ] n ·8nH 2 O [ 69 ], and K 3 n {[Rh 2 (µ–O 2 CCH 3 ) 4 ] 2 Co(CN) 6 } n [ 70 ].…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…All the Rh-Rh distances are indicative of a single bond between Rh(II) ions. Rh-Rh and Rh-N distances are similar to those found in other related compounds such as (PPh 4 ) 2 n [{Rh 2 (µ–O 2 CCH 3 ) 4 }{M(CN) 4 }] n (M = Ni, Pd, Pt) [ 61 ], K n [Rh 2 (µ–O 2 CR) 4 Au(CN) 2 ] n (R = Me, Et) [ 59 ], (PPh 4 ) n [Rh 2 (µ–O 2 CR) 4 Ag(CN) 2 ] n (R = Me, Ph, CH 2 OEt) [ 60 ], (PPh 4 ) 2 {Rh 2 (μ–O 2 CCMe 3 ) 4 [Ag(CN) 2 ] 2 } [ 60 ], [K(18–crown–6)(H 2 O)] 2 n [K(18–crown–6)(H 2 O) 2 ] n [Rh 2 (µ–O 2 CPh) 4 Fe(CN) 6 ] n ·8nH 2 O [ 69 ], and K 3 n {[Rh 2 (µ–O 2 CCH 3 ) 4 ] 2 Co(CN) 6 } n [ 70 ].…”
Section: Resultssupporting
confidence: 79%
“…This interest is explained due to their structural variety and interesting properties such as magnetism or luminescence [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Following this strategy, our research group has reported the synthesis and characterization of several heterometallic complexes based on cyanidometallate ligands coordinated to the axial positions of the Rh 2 4+ paddlewheel unit [ 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation